#### Answer

4

#### Work Step by Step

$\lim\limits_{x \to 5} \frac{x^2 - 6x + 5}{x -5} = \lim\limits_{x \to 5} \frac{(x - 5)(x-1)}{x -5} = \lim\limits_{x \to 5} x - 1 = 4$

Published by
Cengage

ISBN 10:
1285740629

ISBN 13:
978-1-28574-062-1

4

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.